Conceptualizing critical practice in social work: an integration of recognition and redistribution. Issue 1 (2nd January 2023) - Timor-Shlevin, Shachar
ABSTRACT: In the current construction of critical theory of social work practice, recognition is a central explanatory concept. It informs critical practice as primarily relational, focused on providing respect and visibility for service users, and allowing their voices to be heard. However, while critical political theory emphasizes the ethical commitment to integrating recognition with redistribution, the focus on recognition in social work practice hinders the conceptualization of providing material support as a valuable practice. This gap may lead to the construction of direct social work as irrelevant for people living in poverty and social exclusion, who suffer from a lack of both recognition and redistribution. This article offers an integrated model for critical social work practice in which recognition and redistribution intersect. This model identifies four different types of casework practice: isolated emotional support, isolated material assistance, managerialist withdrawal, and critical practice, and contributes to the construction of a relevant theory of critical practice for social work.